Rain reign - Martin, Ann M., 1955- (Square Fish, 2018)
Autistic fifth-grader Rose Howard, who is fascinated by her own set of rules and a passion for homonyms, sets out on a search for her beloved dog Rain after her father accidentally lets the dog out during a dangerous storm.